Totally endoscopic cartilage tympanoplasty: a hierarchical task analysis. - Fahy, R; Corbett, M; Crotty, T; Chadwick, L; Keogh, I (Journal of Laryngology & Otology, 2023)
Background: Totally endoscopic ear surgery is a novel method of conducting otological surgery. Hierarchical task analysis and the systematic human error reduction and prediction approach ('SHERPA') are valuable tools that can effectively deconstruct the technical and non-technical skills required to successfully complete a surgical procedure. Methods: Twenty-five endoscopic tragal cartilage tympanoplasties were observed, to identify the tasks and subtasks required for completion of totally endoscopic tragal cartilage tympanoplasty. The systematic human error reduction and prediction approach was used to identify the potential risks and methods, to reduce or remediate these risks. Results: A hierarchical task analysis was performed, identifying 8 tasks and 50 subtasks for a safe approach to completing totally endoscopic tragal cartilage tympanoplasty. A risk score for each subtask was calculated to produce a systematic human error reduction and prediction approach and to highlight potential errors. Conclusion: This hierarchical task analysis allowed for quick reference to a correct method of endoscopic tympanoplasty. The systematic human error reduction and prediction approach was employed to reduce the risks associated with undergoing endoscopic tympanoplasty, to improve patient safety.